2015
DOI: 10.1371/journal.pone.0126851
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Niches of Colonisation of Vitis vinifera L. by the Esca-Associated Fungus Phaeoacremonium aleophilum Using a gfp Marked Strain and Cutting Systems

Abstract: IntroductionEsca disease has become a major threat for viticulture. Phaeoacremonium aleophilum is considered a pioneer of the esca complex pathosystem, but its colonisation behaviour inside plants remains poorly investigated.Material and MethodsIn this study, P. aleophilum::gfp7 colonisation was assessed six and twelve weeks post-inoculation in two different types of tissues: in the node and the internode of one year-old rooted cuttings of Cabernet Sauvignon. These processes of colonisation were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 30 publications
4
28
0
Order By: Relevance
“…Grapevine material was collected in vineyards and conditioned as described in Pierron et al (2015a) . One-year-old canes of V. vinifera L. cv.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Grapevine material was collected in vineyards and conditioned as described in Pierron et al (2015a) . One-year-old canes of V. vinifera L. cv.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, the accumulation of suberin in pruning wounds correlates with their susceptibility to infection by Eutypa lata ( Munkvold and Marois, 1995 ) and may participate in trunk defense more than does the accumulation of lignin ( Pouzoulet et al, 2014 ). Discoloration of wood following the annual growth ring ( Mugnai et al, 1999 ) and the occlusion of xylem vessels ( Mori et al, 2001 ; Pierron et al, 2015a ) has also been characterized. More recently, by comparing wounded and inoculated cuttings with wounded and non-inoculated cuttings, Czemmel et al (2015) revealed that, compared with the latter, the former has a lower starch content 2 months post-inoculation with Neofusicoccum parvum .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, diseased plants display an impaired water transport (caused by xylem dysfunction), which in turn leads to a considerable decline of leaf gas exchange and water use efficiency traits (Edwards et al, 2007;Pouzoulet et al, 2014). It was recently demonstrated that the impaired water transport can be caused, at least in part, by P. minimum and P. chlamydospora both growing into the xylem vessel lumens, limiting water transport and inducing the deposition of tyloses as plant defence response (Landi et al, 2012;Pierron et al, 2015).…”
Section: Introductionmentioning
confidence: 99%